Water harvesting technologies in semi-arid and arid areas - Biruk Fikadu Gebreyess; Abayineh Amare (Brawijaya University, 2019)
With the increases in world population, the demand for natural resource like water also increases. Groundwater and surface resources have been used are being utilized quicker than they could be replaced. Thus, water harvesting is an exercise that has been implemented by several countries as a feasible means of water management techniques. The aim of this paper is to review of literature on various types of water harvesting technologies available in different semi-arid and arid areas; to show features of water harvesting technology use and storage mechanisms; and to overview major pros and cons of water harvesting. It is concluded that since there are various water harvesting techniques with their unique characteristics, pros, and cons, it is always crucial to take the local context in to account where the water harvesting techniques are implemented.